Psychology of game playing: Introduction to a special issue - Andrew M. Colman; Briony D. Pulford (Games, 2015)
Game theory has focused attention on different problems at different times in its history. Currently, attention is devoted to investigating how human decision makers with bounded rationality choose strategies in interactive decisions. Behavioral economics, and more generally experimental games, have appeared in the literature with accelerating frequency since 1990, and this cannot continue indefinitely without a proportional expansion of journal space. This Special Issue includes contributions to behavioral economics, experimental games, and evolutionary game theory, using theoretical, experimental, and agent-based modeling techniques.
Keywords: 330; behavioral game theory; experimental games; history of game theory